In Vitro Evaluation of Antioxidant and Lipase Inhibition Properties of Rosella (Hibiscus sabdariffa L.) Flower Kombucha - Aji, Oktira Roka; Putri, Anas Tasya; Handayani, Erisa Budi; Ihsani, Nisa (Universitas Ahmad Dahlan, 2024)
Kombucha, a traditional fermented beverage made from tea, sugar, and a kombucha culture, is known for its unique flavor, aroma, and health benefits. The fermentation process, typically lasting between 8 and 12 days, influences the beverage's physical and chemical properties. While traditionally brewed from tea, alternative substrates like rosella flowers (Hibiscus sabdariffa L.) are also used. Rosella flowers, rich in vitamins and bioactive compounds, have demonstrated potential in combating obesity and exhibiting antioxidant properties. This study aimed to evaluate the chemical and biological characteristics of rosella flower kombucha, particularly its antioxidant and lipase inhibitor activities. The fermentation process led to significant biochemical changes, including a decrease in pH and reducing sugar content, an increase in microbial biomass, and a reduction in ascorbic acid content. The results revealed that rosella flower kombucha had a higher total phenol content and better DPPH radical scavenging activity compared to rosella flower infusion, indicating enhanced antioxidant potential. Additionally, rosella kombucha demonstrated more effective lipase inhibition, suggesting its potential benefits for weight management and metabolic health. These findings emphasize rosella kombucha's potential as a healthful functional beverage, recommending further research in these areas.